Despido intempestivo en los contratos individuales de trabajo y sus garantías constitucionales en el Ecuador - TAYUPANDA CHUCHO, BLANCA GLADYS (2014)
The employer in dismissing untimely worker, is ending without cause or justification employment, which produces the dismissal and is required to pay monetary damages determined in law by failing to comply with this situation creates a number of problems, to violating workers' rights and labor principles guaranteed in the Constitution of the Republic of Ecuador and the Universal Declaration of Human Rights, International Labour Organization, which promotes unemployment and unemployment. This is a violation against the rights of workers, which is fired without cause by removing their only income family, this act of abuse by employers, is typified in our Labour Code, which must be compensated as follows for unfair dismissal which is up to three years of service, with the value of three months' pay and more than three years, with the amount equivalent to one month's salary for each year of service, provided that in no event exceed the value of twenty-five months' pay. This compensation under the Labor Code is insufficient, insolvent for workers who keep their families, their homes forcibly causing their children go to seek work in the streets. But if the compensation was reasonable recognizing its workforce, would be an economic incentive, since it would have to survive until you find a new job, but unfortunately it does not, the employer fires without any worker will In Ecuador, especially in the province of Orellana, Francisco de Orellana Canton, major changes and daily problems that affect social development, such as unfair dismissal in individual employment contracts, both doctrine and universal jurisprudence evidenced understood as the unfair dismissal, all abusive and unfair to an employee leaving employment licensing householders, by the employer, and the job is the daily livelihood of the family, which gives her children an education. The dismissal without seriously affecting the worker, their family and the country's economy, with unemployment generated by this loophole, which should be discussed in the National Assembly to give effect to the rights of stability, elimination of unemployment, determined in the Constitution, as the Labour Code in Art. 188, does not guarantee the right to a permanent and stable job, so the unfair dismissal provisions of the Labour Code, violates the principles of stability and continued employment. These abuses by employers, is because they have higher charges which empowers arbitrarily dismiss, exceeding the worker his hours of work, occupation change, altering agreements made at the start of your contract, reason why it is very necessary a proposed legal reform to protect workers' rights and improve conditions in the employment relationship between employers and workers